Shari'ah contracts governing debt based Sukuk structures in Islamic capital markets. - Adam Sa'ad, Auwal (Serial Publication Private Limited India, 2014)
The most unique aspect of investment Sukuk is Shari’ah compliance because it differs from other conventional asset class investments.The Shari’ah offers detailed explanationof the Islamic conception of money and capital, the relationship between risk and profit, and the social duties of financial institutions and individuals with regards to Sukuk structures.1 This paper discusses various Shari’ah contracts used to tructure Islamic debt-based Sukuk. The paper is primarily concerned with acceptable and non-acceptable contracts in Islam used for asset securitization. Alongside with some theory of Islamic prohibitory transactions.